(untitled) (BIRDEM Medical Journal, 2019)
Background: Red cell distribution width (RDW) is a routine parameter in fully automated hematology auto analyzer, can give the idea of iron deficiency before haemoglobin and mean corpuscular volume in early iron deficiency or latent stage. Patient can be benefited by doing complete blood count including RDW for the diagnosis of early iron deficiency as a cheaper test than iron profile. This study was aimed to predict early iron deficiency by RDW, mean corpuscular volume and haemoglobin concentration in pregnant women. Methods: In this study, 190 pregnant women were included from Gynae and Obstetric outdoor of Bangabandhu Sheikh Mujib Medical University from august 2008-2009. Complete blood count including haemoglobin percentage, mean corpuscular volume and RDW and iron profile were done. RDW was compared with haemoglobin concentration and mean corpuscular volume in various stages of iron deficiency. Results: RDW was more significant than haemoglobin concentration in latent iron deficiency when haemoglobin level was normal (p<0.05). In mild and moderate iron deficiency anemia, RDW was increased progressively though haemoglobin level was reduced. RDW was more significant than mean corpuscular volume level in latent iron deficiency, mild and moderate iron deficiency anemia. The difference of mean corpuscular volume and RDW was statistically significant (p<0.05) in latent iron deficiency, mild iron deficiency anaemia and moderate iron deficiency anaemia (p value of 0.001, 0.001 and 0.011). In this study RDW had sensitivity 82.3% and specificity 97.4%. haemoglobin concentration and mean corpuscular volume had sensitivity 56.6% and 29.2 % and specificity 90.9% and 98.7 % respectively. Based on the receiver-operator characteristic (ROC) curves RDW had the best area (0.925) under curve compared to haemoglobin and mean corpuscular volume. Conclusion: Latent iron deficiency without other existing disease like haemoglobinopathy, early folate / vit B12 deficiency could be predicted early by increased RDW when haemoglobin concentration and mean corpuscular volume were normal. Birdem Med J 2019; 9(2): 111-116